(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Delinquency and parenting are frequently linked to the effects of additional factors, such as the subject’s gender, color, or ethnicity adolescent. Effects of family structure on crime. Among the family types examined were single mothers, fathers who are single, stepmothers and stepfathers, and intact families. This study demonstrates a strong impact of gender interaction. Thus, the phrase “juvenile delinquency” refers to a wide category that connects teenagers in two important aspects. Firstly, they will always be between the ages of 18 and 24. Secondly, the fact that they were charged with a crime and appeared in court. Numerous things can lead to juvenile delinquency. Peer pressure, being close to violence, intelligence, being around others who are criminals, and specific hereditary features are all factors. This chapter presents the statistical data related to the profile and perception of the respondent and the listed problem. This part of the study discusses the corresponding analysis, presentation, and interpretation of the data result. Researchers explain the overall result gathered from the perspective of parents. The majority of the data is agreed upon by the respondents, and the presents present their perceptions to the researcher. The quality of parental relationships with the juvenile is important in reducing juvenile delinquency trends. Parents’ role model is paramount to juveniles. Punishment by spanking does not necessarily instill discipline in children. On the contrary, this is a contributing factor to delinquency as juveniles translate this to hatred. Most parents do not monitor their juvenile behavior appropriately. As a result, they were unable to identify and curb behavior before getting out of hand. Some juveniles came from a family with both parents but still ended up as juveniles. This means it’s not the mere presence of parents but the quality of interpersonal relationships experienced. In addition, the family rules and regulations need to be developed by both the parents and children.